Pengaruh Brand Ambassador Dan Discount Terhadap Minat Beli Konsumen Di Tokopedia - Fitriyah Izzatul Jannah; Muhammad Ridwan Basalamah; Ratna Tri Hardaningtyas (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This researcher aims to find out (1) the influence of Brand Ambassador on consumer buying interest, (2) the influence Discount on consumer buying interest, the population in this research is Unisma students of the Faculty of Economics and Business 2018 who are consumers at Tokopedia, the number of samples is 90 respondents, the selection technique The sample used is purposive sampling. The data analysis technique in this study is instrument test, normality test, classical assumption test, namely multicollinearity test, heteroscedasticity test, and assumption test of multiple linear regression analysis. The results in this study indicate that the Brand Ambassador variable Discount has a positive and significant effect on consumer buying interest which is 0.000 <0.05. Keyword : Brand ambassador, discount, and consumer buying interest.